Geochemistry - Brownlow, Arthur H. (Englewood Cliffs, New Jersey : Prentice-Hall, 1979)
This text covers the field of geochemistry. It uses a blend of theory, laboratory, and field studies to show how geochemical principles can be used to solve specific geologic problems, and features examples of the application of geochemical principles to the study of natural waters, soil, and sedimentary, igneous, and metamorphic rocks
One. The elements -- Two. Isotope geology -- Three. Thermodynamics -- Four. Water chemistry -- Five. Crystal chemistry -- Six. Organic geochemistry -- Seven. Sedimentary rocks -- Eight. Igneous rocks -- Nine. Metamorphic rocks.
Includes index.
Keywords: HISTORICAL GEOLOGY